Recent Trends in Winter Temperature Extremes in Eastern China and their Relationship with the Arctic Oscillation and ENSO - 陈尚锋 陈文 魏科 (Advances in atmospheric sciences, 2013)
Interannual variations in the number of winter extreme warm and cold days over eastern China （EC） and their relationship with the Arctic Oscillation （AO） and E1 Nifio-Southern Oscillation （ENSO） were investigated using an updated temperature dataset comprising 542 Chinese stations during the period 1961- 2011. Results showed that the number of winter extreme warm （cold） days across EC experienced a significant increase （decrease） around the mid-1980s, which could be attributed to interdecadal variation of the East Asian Winter Monsoon （EAWM）. Probability distribution functions （PDFs） of winter temperature extremes in different phases of the AO and ENSO were estimated based on Generalized Extreme Value Distribution theory. Correlation analysis and the PDF technique consistently demonstrated that interannual variation of winter extreme cold days in the northern part of EC （NEC） is closely linked to the AO, while it is most strongly related to the ENSO in the southern part （SEC）. However, the number of winter extreme warm days across EC has little correlation with both AO and ENSO. Furthermore, results indicated that, whether before or after the mid-1980s shift, a significant connection existed between winter extreme cold days in NEC and the AO. However, a significant connection between winter extreme cold days in SEC and the ENSO was only found after the mid-1980s shift. These results highlight the different roles of the AO and ENSO in influencing winter temperature extremes in different parts of EC and in different periods, thus providing important clues for improving short-term climate prediction for winter temperature extremes.